Edaravone Enhances the Viability of Ischemia/reperfusion Flaps - 张栋益 康深松 张正文 吴蕊 (Journal of Huazhong University of Science and Technology. Medical sciences, 2017)
The purpose of the experiment was to study the efficacy of edaravone in enhancing flap viability after ischemia/reperfusion（IR） and its mechanism. Forty-eight adult male SD rats were randomly divided into 3 groups： control group（n=16）, IR group（n=16）, and edaravone-treated IR group（n=16）. An island flap at left lower abdomen（6.0 cm×3.0 cm in size）, fed by the superficial epigastric artery and vein, was created in each rat of all the three groups. The arterial blood flow of flaps in IR group and edaravone-treated IR group was blocked for 10 h, and then the blood perfusion was restored. From 15 min before reperfusion, rats in the edaravone-treated IR group were intraperitoneally injected with edaravone（10 mg/kg）, once every 12 h, for 3 days. Rats in the IR group and control group were intraperitoneally injected with saline, with the same method and frequency as the rats in the edaravone-treated IR group. In IR group and edaravone-treated IR group, samples of flaps were harvested after reperfusion of the flaps for 24 h. In the control group, samples of flaps were harvested 34 h after creation of the flaps. The content of malondialdehyde（MDA） and activity of superoxide dismutase（SOD） were determined, and changes in organizational structure and infiltration of inflammatory cells were observed by hematoxylin-eosin（HE） staining, apoptotic cells of vascular wall were marked by terminal deoxynucleotidyl transferase-mediated d UTP nick-end labeling（TUNEL） assay, and the apoptotic rate of cells in vascular wall was calculated. The ultrastructural changes of vascular endothelial cells were observed by transmission electron microscopy（TEM）. Seven days after the operation, we calculated the flap viability of each group, and marked vessels of flaps by immunohistochemical staining for calculating the average number of subcutaneous vessels. The results showed that the content of MDA, the number of multicore inflammatory cells and apoptotic rate of cells in vascular wall in the edaravone-treated IR group were significantly lower than those in the IR group. The activity of SOD, flap viability and average number of subcutaneous vessels in the edaravone-treated IR group were significantly higher than those in the IR group. All the differences were statistically significant. The ultrastructure injury of vascular endothelial cells in the edaravone-treated IR group was slighter than that in IR group. It was concluded that edaravone can significantly enhance IR flap viability and protect flap vessels, which is related to scavenging oxygen free radicals, reducing the consumption of SOD, reducing the extent of lipid peroxidation and inflammation, and protecting functional structure of vessels in the early stages of reperfusion.